"We can love one another in other ways": Collaborating with James Baldwin on a Screenplay of Giovanni's Room. (September 2019) - Raeburn, Michael
Abstract : The author discusses his personal relationship with James Baldwin, recounting their collaboration on a film script for an adaptation of Giovanni's Room .